Laporan Kasus: Transarterial Chemoembolization (Tace) Sebagai Terapi Pilihan Pada Karsinoma Hepatoselular - Sherly Eva Wijayaningrum; Firman Parulian Sitanggang; Putu Patriawan (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Hepatocellular carcinoma (HCC) is the most common primary tumor of the liver and occupies the top 10 most cancers in Indonesia. Men are likely to develop HCC, and 90% cases of HCC develop in the background of chronic liver disease, which associates with hepatitis B and C virus infection. There are numerous treatment options for HCC, however in intermediate-advanced stage, palliative treatment such as transarterial chemoembolization (TACE) and systemic chemotherapy are the management of choice. A 51 years old male with HCC based on history, physical examination, radiology and laboratory result was referred to interventional radiology department for TACE consideration. Barcelona Clinic Liver Cancer (BCLC) B was concluded in this patient after thorough evaluation. There was history of hepatitis B infection, ascites, low albumin level, high AFP, and from Abdominal CT Scan with contrast showed large lobulated mass on the right lobe, without evidence of portal vein thrombosis. TACE was eligible and done using mixed of doxorubicin 50 mg and lipiodol, and embolization using gel foam. After 8 weeks CT evaluation was done and showed increase area of tumor necrosis, while tumor size was stable. Necrosis area expansion is the standard used for evaluating this patient which fell into partial response criteria. TACE is a palliative therapy of choice in accordance with BCLC B recommendation. Evaluation of TACE performance is more optimal by assessing the size of necrosis area compared to mass measurement.